ปัจจัยที่ส่งผลต่อการมีส่วนร่วมของสมาชิกสหกรณ์การเกษตร ในเขตพื้นที่ภาคกลาง: Factors Affecting to Participation of Agricultural Cooperatives Members in Central Region - กิตตินรรัตน์, จักรพันธ์; พหลภาคย์, จุฑาทิพย์ (Journal of Applied Economics and Management Strategy, 2014)
การวิจัยเรื่องการมีส่วนร่วมของสมาชิกสหกรณ์ในภาคการเกษตรเขตพื้นที่ภาคกลาง มีวัตถุประสงค์เพื่อศึกษาปัจจัยที่มีอิทธิพลต่อการมีส่วนร่วมของสมาชิกกับสหกรณ์ เนื่องจากสหกรณ์เป็นองค์กรของสมาชิก ที่ดำเนินงานโดยสมาชิก และทำเพื่อสมาชิก ด้วยเหตุนี้ความสำเร็จทั้งปวงของสหกรณ์นั้น จึงเกิดขึ้นได้จากการเข้ามามีส่วนร่วมในการดำเนินงาน การทำธุรกิจกับสหกรณ์ และการสนับสนุนสหกรณ์ของสมาชิกการได้มาซึ่งข้อค้นพบถึงเหตุปัจจัยของการมีส่วนร่วมของสมาชิกกับสหกรณ์ จะเป็นประโยชน์อย่างยิ่งต่อหน่วยงานที่เกี่ยวข้องในการส่งเสริมการมีส่วนร่วมของสมาชิกกับสหกรณ์การเกษตร อันจะทำให้สหกรณ์การเกษตรมีความเข้มแข็ง และประสบผลสำเร็จ โดยการศึกษานี้ จะเป็นการวิจัยเชิงปริมาณ ทำการเก็บรวบรวมข้อมูลโดยใช้แบบสอบถามจากสมาชิกของสหกรณ์การเกษตรในเขตภาคกลาง อันเป็นพื้นที่ซึ่งมีสหกรณ์การเกษตรอยู่จำนวนมาก และมีบทบาทสำคัญต่อการพัฒนาฐานะทางเศรษฐกิจของประชาชนในภาคนี้ โดยสุ่มตัวอย่างจำนวน 230 ราย ด้วยวิธีการสุ่มแบบหลายขั้นตอน และทำการทดสอบสมมติฐาน โดยใช้การวิเคราะห์เส้นทาง (Path Analysis) ร่วมกับการวิเคราะห์ถดถอยแบบขั้นตอน ผลการวิจัยที่ได้พบว่า สมาชิกส่วนใหญ่เป็นเพศชาย มีอายุเฉลี่ย 51 ปี จบชั้นประถมปลาย มีสมาชิกในครัวเรือนประมาณ 5 คน ในด้านเศรษฐกิจ พบว่า ส่วนใหญ่มีอาชีพทำการเกษตร รองลงมา คือ การรับจ้าง โดยพื้นที่การผลิตที่สมาชิกส่วนใหญ่ใช้ประโยชน์เป็นที่ดินที่ได้สิทธิใช้ฟรี โดยสมาชิก ส่วนใหญ่มีระดับการครองชีพปานกลาง และไม่มีปัญหาทางการเงิน ในด้านความรู้ความเข้าใจต่อการสหกรณ์ พบว่า สมาชิกสหกรณ์ที่เป็นตัวอย่าง ส่วนใหญ่มีความรู้และความเข้าใจเกี่ยวกับการสหกรณ์ในระดับปานกลาง ในด้านทัศนคติพบว่า สมาชิกส่วนใหญ่มีทัศนคติต่อสหกรณ์การเกษตรในระดับปานกลางค่อนข้างสูง ในด้านการตัดสินใจสมัครเข้าเป็นสมาชิกสหกรณ์ พบว่า สมาชิกตัวอย่างส่วนใหญ่ตัดสินใจเข้าเป็นสมาชิกสหกรณ์ด้วยตัวเอง ซึ่งส่วนใหญ่มีความคาดหวังที่จะใช้บริการธุรกิจสินเชื่อ ในด้านการมีส่วนร่วมของสมาชิกกับสหกรณ์ พบว่า ส่วนใหญ่เข้าไปมีส่วนร่วมในกิจกรรมและทำธุรกิจร่วมกับสหกรณ์ในระดับปานกลาง ผลจากการวิเคราะห์ความสัมพันธ์ระหว่างปัจจัยต่างๆที่มีอิทธิพลต่อการมีส่วนร่วมของสมาชิกกับสหกรณ์ พบว่า ปัจจัยส่วนบุคคล ได้แก่ เพศ การมีตำแหน่งและหน้าที่ในสังคม การได้รับข้อมูลข่าวสารจากสหกรณ์ ปัจจัยทางเศรษฐกิจ ได้แก่ พื้นที่การผลิต ปริมาณธุรกิจที่ทำร่วมกับสหกรณ์ เงินปันผลหรือเงินเฉลี่ยคืน และ ปัจจัยทางด้านจิตวิทยา ได้แก่ ทัศนคติ ความรู้และความเข้าใจในหลักการและวิธีดำเนินธุรกิจของสหกรณ์มีอิทธิพลพลต่อการมีส่วนร่วมของสมาชิกกับสหกรณ์ แต่อายุและจำนวนปีการศึกษา พบว่าไม่มีผลโดยตรงแต่มีผลโดยอ้อมต่อการมีส่วนร่วมของสมาชิกกับสหกรณ์ผ่านทัศนคติและความรู้ความเข้าใจในการสหกรณ์ This research on participation of Agricultural Cooperatives members in central regions aims to examine factors affecting participation by members of Agricultural Cooperatives. The Agricultural Cooperatives are run by the members for the members. For this reason, the success of Agricultural Cooperatives stems from the participation and support of members. Therefore, the study on factors related to the participation of members of Agricultural Cooperatives would be very useful for relevant agencies to promote the participation of members of Agricultural Cooperatives and strengthen the Agricultural Cooperatives’ achievement. This quantitative research collected data by using questionnaires with the members of Agricultural Cooperatives in central region. This area contains numerous Agricultural Cooperatives which have played an important role in economic development. The total 230 samples were randomized by applying multi-stage sampling and then a hypothesis test was conducted by utilizing path analysis and stepwise regression analysis. The results found that most members were male at the age of 51 and graduated from upper primary school. There were 5 members in their families. In aspect of economy, most of them were agriculturalists, followed by employees. Most members utilized the production area for free. Besides, their living standard was at moderate level and they did not have any financial problem. In terms of understanding on the Agricultural Cooperatives, most samples had knowledge and understanding on this topic at moderate level. Moreover, their attitudes towards the Agricultural Cooperatives were at moderate to high level. When considering a decision to apply for the member of Agricultural Cooperatives, most samples made the decision by themselves and they mostly expected to use loan service. In aspect of the members’ participation in the Agricultural Cooperatives, most of them took part in activities and businesses of the Agricultural Cooperatives at moderate level. According to the analysis of relationship between several factors affecting the members’ participation in the Agricultural Cooperatives, the findings indicated that some personal factors such as sex, social position, information from Agricultural Cooperatives, economical factors including production area, amount of business joined with Agricultural Cooperatives, dividend or return average money, and psychological factors consisting of attitude, knowledge understanding on principles and approaches for running the business of Agricultural Cooperatives had an influence on the members’ participation in the Agricultural Cooperatives. However, age and education had no direct effect but they indirectly affected the members’ participation through the attitude, knowledge and understanding on the Agricultural Cooperatives.